PENGEMBANGAN MEDIA EDUCAPLY UNTUK EMNINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN PKN KELAS II SD IT AL-HABIB - Ajeng yuanda; Ahmad Landong; Della Pradita; Dinda Absi Harahap; Eca Fathanah; Irma Melati; Mayumi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a digital evaluation tool for Pancasila Education on the topic of rules at home and school for second-grade elementary students. The research uses the Research and Development (R&D) method with the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The results of the needs analysis indicate that students' learning interest is relatively low due to the use of conventional evaluation methods that are less interactive. Therefore, a digital evaluation based on a contextual approach was developed using the Educaplay platform. The product was validated by media experts and material experts before implementation. The findings show that the digital evaluation is valid, feasible, and effective in increasing students' motivation and understanding. The use of interactive and visual-based digital evaluation helps students comprehend learning materials more easily and enhances engagement in the learning process. This study implies that digital evaluation can be an innovative solution in improving learning assessment in elementary schools.